Pertumbuhan Curah Enterococcus faecalis Id 6017 dan Kemampuan Dekolorisasi Reactive Red-2 pada Medium yang Mengandung Gliserol - V. I. Meitiniarti; Morina M. Napitupulu; K. H. Timotius (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2004)
Enterococcus faecalis ID 6017 can utilize glycerol as the source of carbon and energy for its growth. The present of glycerol in the medium containing Reactive Red-2 not only influenced its growth but also its ability to decolorize Reactive Red-2. The aim of this study was to investigate the growth of  Enterococcus faecalis (E. faecalis) and its ability to decolorize Reactive Red-2. The microbe was grown in batch system with three different growth medium, i.e. medium which contained (i) 1.643 g/l glycerol and 0.08 g/l reactive red-2, (ii) 1.643 g/l glycerol, and (iii) 0.08 g/l Reactive Red 2. The result of this study showed that the growth of  E. faecalis and its ability to decolorize Reactive Red-2 on medium contained glycerol was better than without glycerol. E. faecalis could not growth and decolorized Reactive Red-2 on medium without glycerol.